Bamboo - Conservation, diversity, ecogeography, germplasm, resources utilization and taxonomy: Proceedings of training course cum workshop, 10-17 May 1998, Kunming and Xishuangbanna, Yunnan, China - Rao, A.N.; Ramanatha Rao, V.; International Plant Genetic Resources Institute (1999)
The incentive to organize this training course cum workshop arose as a response to consolidate the ongoing research in different Asian countries on bamboo conservation and genetic improvement. Also an opportunity was created for many of the researchers from various Asian countries to visit Yunnan Province in China and particularly Xishuangbanna Botanic Garden where an extensive bamboo germplasm collection is maintained that represents Indo Malayan, Southeast Asian, Himalayan and East Asian bamboo species that reveal many intergeneric and interspecific variations. The collection also includes some of the biggest bamboos of the world. Many of the bamboo species present are yet to be scientifically identified which also is the situation in most of the Asian countries.